Posługa słowa związana z sakramentem pokuty i pojednania - Twardy, Jan (Studia Pastoralne, 2007)
Penitential preaching arises from the Scriptures and Tradition of the Church. The significant development of this form of word ministry took place in the Middle Ages, when preachers often spoke about sins and appealed for conversion, founding grounds of it in eschatology. Nowadays, it is advisable to speak often and more about the sacrament of penance and reconciliation – referring to revelation and anthropology. It is always necessary to remind believers about the essence and fatal effects of sin – either in a homily concerning the sacrament of penance, as well as in a penitential preaching in the whole; in the same way, it is always actual to stress the endless God’s mercy, redemptive effects of divine grace – and to appeal to true conversion and compensation for the evil that has been done. There are many occasions for preaching about penance and reconciliation during the liturgical year, especially during Lent and at Easter time. such religious issues come from the Liturgy of the Word for Sundays and feast days and is an essence of liturgy of the Mass. All forms of cyclical ministry (such as various retreats, parish missions, days of meditation, the Paschal Triduum, along with examination of conscience) are also closely connected with the sacrament of penance and reconciliation. It is also obvious that the priest himself should be a man of penance, this would enable him to speak with conviction and testify to God’s endless mercy. It is also advisable to do research on contemporary word ministry – paying special attention to its relation with the sacrament of penance and reconciliation. As a warning to Polish priests should be the currently wide-spread conviction in many western countries that confession is not necessary, resulting in people often going to Communion without the sacrament of penance.